2023
DOI: 10.1371/journal.pone.0288370
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hypothermic storage of oocytes of the European common frog Rana temporaria in a gas mixture of oxygen and carbon monoxide

Abstract: The maximum hypothermic storage time of amphibian oocytes is several hours, which is due to the peculiarities of the structure of the cell envelope. The authors of this paper have already demonstrated the possibility of increasing the storage period of unfertilized oocytes of the common frog (Rana temporaria) up to 5–7 days. The aim of the current study was to determine the possibility of using a 6.5 atm gaseous mixture of carbon monoxide and oxygen, for prolonged hypothermic preservation of unfertilized oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Dry storage of cool-temperate anuran oocytes at 4°C in Eppendorf tubes, to prevent dehydration and to maintain ionic stasis, over five days maintained 70% fertility and 40% hatch rates, with some fertility and development extended to eight days [312]. Gagarinskiy et al [313] showed that a 6.5 atm gaseous mixture of carbon monoxide and oxygen doubled the refrigerated storage viability of the unfertilised oocytes of a cool temperate anuran, compared with controls when fertilised over eight days. However, from four to eight days of storage the hatch rate declined to a low level like that of controls.…”
Section: Appendix 2 Oocytes Viability Period and Storage Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry storage of cool-temperate anuran oocytes at 4°C in Eppendorf tubes, to prevent dehydration and to maintain ionic stasis, over five days maintained 70% fertility and 40% hatch rates, with some fertility and development extended to eight days [312]. Gagarinskiy et al [313] showed that a 6.5 atm gaseous mixture of carbon monoxide and oxygen doubled the refrigerated storage viability of the unfertilised oocytes of a cool temperate anuran, compared with controls when fertilised over eight days. However, from four to eight days of storage the hatch rate declined to a low level like that of controls.…”
Section: Appendix 2 Oocytes Viability Period and Storage Environmentmentioning
confidence: 99%
“…However, from four to eight days of storage the hatch rate declined to a low level like that of controls. Therefore, the causes of oocyte loss of viability are ions or proteins diffusing from the gel that are needed for sperm motility or oocyte metabolism [314][315][316], or damage to the cell envelope [313].…”
Section: Appendix 2 Oocytes Viability Period and Storage Environmentmentioning
confidence: 99%